Clinical workflow in medical additive manufacturing (Transactions on Additive Manufacturing Meets Medicine, 2019)
Additive Manufacturing allows for the personalized production of medical models, surgical guides and implants. While the potential for AM in medicine is well known, the implementation of AM in clinical settings remains a challenge since it involves multiple independent parties, technologies and software tools. Recent advances in digitalization allow for more cohesive processes in the AM workflow. We review possible workflow implementations involving state-of-the-art printing technologies and materials, highlighting communication and legal issues.
Keywords: personalized